(untitled) (Italiano LinguaDue, 2021)
Il contributo analizza l’Easy Phraseology, for the Use of Young Ladies, Who Intend to Learn the Colloquial Part of the Italian Language di Giuseppe Baretti in prospettiva glottodidattica, considerando tanto la facies linguistica quanto gli aspetti socio-pragmatici tematizzati nei dialoghi; entrambe le componenti erano ugualmente fondamentali per l’apprendimento dell’italiano, non solo da parte di stranieri. Si sostiene, infatti, che la ripubblicazione primo-ottocentesca dell’opera in Italia abbia rifunzionalizzato il testo per il pubblico italiano dialettofono, proponendo di fatto un modello alternativo alla “lingua arbitraria” parlata, deprecata da Baretti medesimo. An antidote to the “arbitrary language”? The colloquial Italian in Giuseppe Baretti’s Easy phraseology This paper analyzes the Easy Phraseology, for the Use of Young Ladies, Who Intend to Learn the Colloquial Part of the Italian Language by Giuseppe Baretti from a glottodidactic point of view, considering both the linguistic and the socio-pragmatic aspects which are thematized in the dialogues. Both components were equally fundamental for learning Italian, not only by foreigners. It is argued, in fact, that the early-nineteenth-century republication of the work in Italy re-functionalized the text for the Italian dialect-speaking public, effectively proposing an alternative model to the spoken "arbitrary language", deprecated by Baretti himself.